Pengaruh Variasi Diameter Elektroda E7018 Terhadap Kekuatan Tarik, Kekerasan, dan Struktur Mikro Pengelasan pada Baja Karbon Rendah Jenis SS400 dengan Metode SMAW - Rizal Abdul Azis; Suharno Suharno; Herman Saputro (Jurnal Teknik, 2019)
Metal welding by the welding method has weaknesses including the decrease in strength of the material and the results of residual stress, as well as the presence of cracks due to the welding process. The purpose of this research is to know the effect of variations in the diameter of the electrode E7018 to tensile strength, hardness, and microstructure on alloysteel SS400 before (raw material) and after welding using welding methodes Shileded Metal Arc Welding (SMAW) methode. This research uses experimental methode. Technique of data analysis used is the comparative descriptive. Based on the results of the reseach, it can be conclude that the result of the micro structure test showed an inrease perlit structure after welding. On raw material, ferrit structure looks prevalent but on welding result using SMAW welding methods with the variation in the diameter of the electrode 2.6 mm, 3.2 mm, and 4.0 mm showed that the ferrit decreases on each specimen, so the perlite structure is very dominating. Value of tensile strength on the welding result showed a difference in tension and strain. Specimen with a diameter of electrode 4.0 mm have a higher tension level and strain is 471.11 MPa and 24.98% if compared to the electrode diameter 3.2 mm specimen is 470.15 MPa and 24.81%, and the electrode diameter 2.6 mm is 462.42 MPa and 20.57%. This research shows that the welding using diameter variation of electrode changed value of the tensile strength, micro structure and effected on the value of hardness alloy Steel SS400.